IMPROVING JAVANESE LANGUAGE SCRIPT LEARNING THROUGH THE QUIZIZZ GAME AT STATE ELEMENTARY SCHOOL KULON 1 GONDANGLEGI - MALANG - Sulfadiyah, Atik (JURALIANSI: Jurnal Lingkup Anak Usia Dini, 2025)
Javanese language learning has levels including ngoko (rough) and krama (polite). The purpose of this research is to describe the form of Javanese language learning and the results of Javanese language learning through the Quizizz game. The research methodology uses classroom action research with data collection techniques of observation, interviews, and documentation. Actions were carried out over two cycles. The results of the research and learning form of Javanese language learning introduce the Javanese script as the basis of the language, then the ngoko (rough) and krama (polite) language. This level is learned repeatedly in each cycle meeting. Understanding Javanese language has a complex level of difficulty, which is much easier if packaged through a quiz game. Learning using the Quizizz game technique. Where, the Quizizz game can be used as a distance learning mediator. This means it can be used while studying at home but still under the supervision of educators. Packaging the concept design through multiple choice with direct assessment. The percentage results of the first cycle reached 50.23% where the learning concept uses the Javanese script. In addition, learning in the second cycle stage reached 81.94% by introducing the ngoko and krama language types. It can be concluded that complex learning can be packaged through digital games so that the learning concept can be carried out in a fun way within the specified learning time.